Method for treating polymer implanted in-vivo material sample
By using nitrate solution soaking and coating technology containing yttrium, tantalum, zirconium, silver and strontium metal ions in polymer implantation materials, the problem of insufficient biocompatibility and antibacteriality of the material is solved, and the material is realized Improved stability and antibacterial properties, suitable for alloy-containing polymer implant materials.
Patent Information
- Application Number
- CN202411399370.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Existing polymer implanted in vivo materials have shortcomings in terms of biocompatibility, stability and antibacteriality, which limits its application scope.
Immerse nitrate solution containing yttrium, tantalum, zirconium, silver and strontium metal ions, and cover the surface of the polymer matrix material with alternating layers of pure titanium, pure tantalum and tantalum yttrium to improve the biocompatibility and antibacteriality of the material. sex.
It significantly improves the corrosion resistance, antibacteriality and toughness of the material, enhances the degree of fusion with the human body and tissue regeneration effect, reduces the risk of bacterial infection, and extends the stability of the material.
Smart Images

Figure BDA0005074780730000101
Abstract
Description
Technical Field
[0001] The invention relates to the application field of implantable materials, and in particular to a method for processing polymer implantable material samples. Background Art
[0002] Polymer implant materials can be widely used in artificial blood vessels, artificial bones and joints, surgical sutures and other aspects. The scope of polymer implant materials themselves is also relatively wide, such as bio-inert polymer materials, common materials include: polyethylene, polypropylene, polyacrylate, aromatic polyester, polysulfone, polytetrafluoroethylene (PTFE), silicone rubber, polyurethane (PU), polyetheretherketone (PEEK), polyvinyl chloride (PVC), polystyrene (PS), etc. Another example is biodegradable polymer materials, including: collagen, aliphatic polyester, chitin, cellulose, polyamino acid, polyvinyl alcohol, polylactic acid (PLA), polycaprolactone (PCL), etc.
[0003] However, during the use of the above materials, there are often problems such as insufficient biocompatibility, stability, and antibacterial properties, which directly limit the application of the above materials.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a method for processing polymer implant material samples, which improves the biocompatibility and antibacterial properties of the material itself and fundamentally improves the stability of the material itself by soaking it in a solution containing metal ions and coating it.
[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0007] The present invention provides a method for processing a polymer implant material sample, comprising the following steps:
[0008] The polymer matrix material is immersed in a nitrate solution containing metal ions at a temperature of 40-50° C. for more than 10 hours, and the surface is coated after the immersion, wherein the metal ions include any one or more of yttrium, tantalum, zirconium, silver, and strontium metal elements, and the polymer matrix material includes at least an alloy;
[0009] The coating includes a pure titanium layer as an innermost layer, a pure tantalum layer as an intermediate layer, and a tantalum-yttrium alternating layer as an outermost layer.
[0010] In the scheme of the present invention, if the matrix material only contains polymer materials, it is not suitable for the scheme of the present invention. The matrix material is required to have a certain alloy component, because the hardness and support of the matrix are sufficient to carry out the subsequent immersion and coating processes, ensuring the smooth progress of the subsequent processes.
[0011] During the soaking process, the reason for choosing a metal ion solution containing any one or more of yttrium, tantalum, zirconium, silver, and strontium is that each of the above metal elements plays a vital role in the better integration of the implant and the human body. Tantalum itself has good corrosion resistance and good toughness. Silver has good antibacterial properties and can improve the integration of the implant in the body and reduce the risk of bacterial infection. The addition of yttrium, zirconium and strontium metals can cooperate with tantalum to improve the toughness of the material itself, reduce rejection, promote the integration of the human body and the implant, and improve the body's own tissue regeneration. In addition to considering the possibility of mutual compatibility, the above metal elements also consider the improvement of the performance of the material itself during the selection process. Because the requirements for implant materials for antibacterial and anti-pollution properties are extremely high, it is necessary to be cautious when choosing metal ions. It is necessary to choose metals that are beneficial to the human body and can reduce rejection reactions, and also consider the improvement of the performance of the material itself after mutual cooperation.
[0012] Preferably, as a further feasible solution, the composition of the metal ions includes: by mass, 1-5 parts of yttrium, 0.5-2 parts of tantalum, 5-10 parts of zirconium, 1-3 parts of silver, and 0.5-1 parts of strontium.
[0013] Preferably, as a further feasible solution, in parts by mass, yttrium is 2-3 parts, tantalum is 1-1.5 parts, zirconium is 7-9 parts, silver is 2-2.5 parts, and strontium is 0.7-0.9 parts.
[0014] Preferably, as a further feasible solution, in parts by mass, yttrium is 2.5 parts, tantalum is 1.2 parts, zirconium is 8 parts, silver is 2.2 parts, and strontium is 0.8 parts.
[0015] Among the above schemes, the better scheme is a nitrate solution containing yttrium, tantalum, zirconium, silver and strontium in the metal ion solution, because only when the above metal ions exist at the same time can the functional complementarity be achieved. The better scheme is to match the above metal ions in a certain mass ratio. In fact, although tantalum mainly improves the toughness of the material, silver mainly improves the antibacterial property of the material, and the addition of yttrium, zirconium and strontium metals promotes biocompatibility, they also have cross-promoting effects in actual function. Because too much silver itself will be toxic, it will also rely on yttrium and other metals to indirectly play a common antibacterial effect at the same time. At the same time, the addition of other metals can further help the stability and toughness of the material itself. Therefore, given that each metal ion does not play a single role in a certain aspect, it is more necessary to pay attention to the amount added to ensure the mutual compatibility between the components.
[0016] Preferably, as a further implementable scheme, the concentration of the nitrate solution is 20-30wt%, and more preferably can be 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt% and the like. The concentration of the salt solution for immersion should not be too high, otherwise it will have a certain impact on the matrix material. Micro-heating can promote the interaction between the metal ions and the matrix material after immersion, and the immersion time can be appropriately extended to improve the effect.
[0017] Preferably, as a further implementable solution, the thickness ratio of the pure titanium layer, the pure tantalum layer and the tantalum-yttrium alternating layer is 1:(2-3):(2-5).
[0018] Preferably, as a further implementable solution, the number of alternating layers of the tantalum-yttrium alternating layers is 3-8 layers, wherein the tantalum layer in the tantalum-yttrium alternating layers is attached to the pure tantalum layer.
[0019] Preferably, as a further implementable solution, the thickness of the pure titanium layer is 0.05-0.08 μm, preferably 0.07 μm, and may also be 0.06 μm, 0.075 μm, 0.055 μm, 0.065 μm, 0.075 μm, and so on.
[0020] Preferably, as a further feasible solution, the content of tantalum pentoxide in the tantalum-yttrium alternating layer is 60-70wt%, and the rest is yttrium trioxide.
[0021] Preferably, as a further feasible solution, each layer of the coating is sputter-coated using a corresponding target material.
[0022] The purpose of coating the surface of the substrate after immersion is to further improve the biocompatibility and antibacterial properties of the implant material, especially by utilizing the chemical bonds formed between the metal elements in the three layers of the film, which can make the film itself denser. The structure of the film mainly utilizes the pure titanium layer and the pure tantalum layer in the inner layer to resist corrosion and improve stability. The innermost layer is a pure titanium layer because titanium has better corrosion resistance than tantalum, and the outer layer is a tantalum-yttrium alternating layer, which is also to make the film layers containing tantalum close together and have stronger interaction force. The alternating layer setting method is more effective than the single film layer method. It can greatly improve the effect of mutual filling, and it is also more conducive to the formation of grain structure between metal elements by stacking layers. Of course, considering the production cost of the entire sample and its own performance, the number of alternating layers should not be too many. The number of alternating layers of tantalum and yttrium is 3-8 layers, and the corresponding number of layers will be selected according to the different mechanical properties of the substrate. In addition, in terms of the thickness ratio of each film layer, the innermost pure titanium layer is relatively thin, because if the thickness is too thick, its ductility is poor and the bonding with the substrate is not good. Then the two layers located on the outside can be relatively thicker to improve the performance of the metal elements in the film layer.
[0023] The reason why the tantalum content is higher in the alternating layer is that yttrium trioxide mainly plays an auxiliary role, so its content will be slightly lower.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The polymer implant material sample processing method of the present invention is very suitable for polymer implant materials containing a certain alloy component in the matrix, and can improve a series of properties of the material itself, such as corrosion resistance, antibacterial property and toughness.
[0026] (2) During the processing of the polymer implant material of the present invention, the material is immersed in a solution containing multiple metal ions, which fully considers the possibility of mutual compatibility of various metal elements and the performance improvement of the material itself.
[0027] (3) The polymer implant material of the present invention is coated on the surface of the substrate after being soaked, in order to further improve the biocompatibility and antibacterial properties of the implant material. DETAILED DESCRIPTION
[0028] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0029] Example 1
[0030] Step 1: dissolving 1 g of yttrium nitrate, 2 g of tantalum nitrate, 5 g of zirconium nitrate, 3 g of silver nitrate and 0.5 g of strontium nitrate in deionized water to prepare a nitrate aqueous solution containing yttrium, tantalum, zirconium, silver and strontium ions, wherein the solute concentration in the nitrate aqueous solution is controlled between 20-25 wt %;
[0031] Step 2: Select a bone replacement implant material formed by a composite of TC4 titanium alloy and high molecular polyethylene as a matrix, immerse the matrix in the nitrate aqueous solution formed in the above step 1, heat to 40° C., immerse for 10 hours and perform ultrasonic treatment at the same time, and after treatment, take out the matrix and wipe it until the surface is completely dry;
[0032] Step three: Then put the substrate on the sample table in the workbench cavity, and evacuate the cavity, then introduce argon gas, clean the substrate for 20 minutes, then power on the titanium target to start coating the pure titanium layer. During coating, the workbench and the sample table rotate, and the substrate rotates, with the workbench speed being 1r / min, the sample table speed being 20r / min, and the substrate speed being 10r / min. The current on the titanium target is 10-15A, and the coating time is 10min, forming a pure titanium layer on the surface of the substrate, with a thickness of 0.05μm;
[0033] Step 4: Then the tantalum target is also passed through a current of 10-15A, and the coating time is 20 minutes to form a pure tantalum layer outside the pure titanium layer with a thickness of 0.1μm;
[0034] Step 5: The sputtering of the alternating layers is carried out by passing current through the alternating tantalum target and the yttrium target. The alternating layers formed are 3 layers. The tantalum target is first sputtered to make it adhere to the pure tantalum layer. The coating time is 30 minutes and the total thickness is 0.1 μm. The two tantalum layers are thicker than the yttrium layers to ensure that the content of tantalum pentoxide is 60wt% and the content of yttrium trioxide is 40wt%;
[0035] Step 6: After the coating is completed, stop supplying current to the target material, cool it down, and release the air to obtain a product with a three-layer composite film coated on the surface of the substrate.
[0036] Example 2
[0037] Step 1: dissolving 5 g of yttrium nitrate, 0.5 g of tantalum nitrate, 10 g of zirconium nitrate, 1 g of silver nitrate and 1 g of strontium nitrate in deionized water to prepare a nitrate aqueous solution containing yttrium, tantalum, zirconium, silver and strontium ions, wherein the solute concentration in the nitrate aqueous solution is controlled between 25 and 30 wt %;
[0038] Step 2: Select a bone replacement implant material formed by a composite of TC4 titanium alloy and high molecular polyethylene as a matrix, immerse the matrix in the nitrate aqueous solution formed in the above step 1, heat to 50° C., immerse for 15 hours and perform ultrasonic treatment at the same time, and after treatment, take out the matrix and wipe it until the surface is completely dry;
[0039] Step three: Then put the substrate on the sample table in the workbench cavity, and evacuate the cavity, then introduce argon gas, clean the substrate for 20 minutes, then power on the titanium target to start coating the pure titanium layer. During coating, the workbench and the sample table rotate, and the substrate rotates, with the workbench speed being 1r / min, the sample table speed being 20r / min, and the substrate speed being 10r / min. The current on the titanium target is 10-15A, and the coating time is 12min, forming a pure titanium layer on the surface of the substrate, with a thickness of 0.06μm;
[0040] Step 4: Then the tantalum target is also passed through a current of 10-15A, and the coating time is 25 minutes to form a pure tantalum layer outside the pure titanium layer with a thickness of 0.18μm;
[0041] Step 5: The sputtering of the alternating layers is carried out by passing current through the alternating tantalum target and the yttrium target. The alternating layers are 8 layers. The tantalum target is first sputtered to make it adhere to the pure tantalum layer. The coating time is 35 minutes and the total thickness is 0.3 μm. The thickness of the tantalum layer is thicker than that of the yttrium layer to ensure that the content of tantalum pentoxide is 70wt% and the content of yttrium trioxide is 30wt%;
[0042] Step 6: After the coating is completed, stop supplying current to the target material, cool it down, and release the air to obtain a product with a three-layer composite film coated on the surface of the substrate.
[0043] Example 3
[0044] Step 1: dissolving 2.5 g of yttrium nitrate, 1.2 g of tantalum nitrate, 8 g of zirconium nitrate, 2.2 g of silver nitrate and 0.8 g of strontium nitrate in deionized water to prepare a nitrate aqueous solution containing yttrium, tantalum, zirconium, silver and strontium ions, wherein the solute concentration in the nitrate aqueous solution is controlled between 25-30 wt %;
[0045] Step 2: Select a bone replacement implant material formed by a composite of TC4 titanium alloy and high molecular polyethylene as a matrix, immerse the matrix in the nitrate aqueous solution formed in the above step 1, heat to 45° C., immerse for 15 hours and perform ultrasonic treatment at the same time, and after treatment, take out the matrix and wipe it until the surface is completely dry;
[0046] Step three: Then put the substrate on the sample table in the workbench cavity, and evacuate the cavity, then introduce argon gas, clean the substrate for 20 minutes, then power on the titanium target to start coating the pure titanium layer. During coating, the workbench and the sample table rotate, and the substrate rotates, with the workbench rotating at 1r / min, the sample table rotating at 20r / min, and the substrate rotating at 10r / min. The current on the titanium target is 10-15A, and the coating time is 15min, forming a pure titanium layer on the surface of the substrate, with a thickness of 0.07μm;
[0047] Step 4: Then the tantalum target is also passed through a current of 10-15A, and the coating time is 25 minutes to form a pure tantalum layer outside the pure titanium layer with a thickness of 0.18μm;
[0048] Step 5: The sputtering of the alternating layers is carried out by passing current through the alternating tantalum target and the yttrium target. The alternating layers are 5 layers. The tantalum target is first sputtered to make it adhere to the pure tantalum layer. The coating time is 30 minutes and the total thickness is 0.28μm. The thickness of the tantalum layer is thicker than that of the yttrium layer to ensure that the content of tantalum pentoxide is 65wt% and the content of yttrium trioxide is 35wt%;
[0049] Step 6: After the coating is completed, stop supplying current to the target material, cool it down, and release the air to obtain a product with a three-layer composite film coated on the surface of the substrate.
[0050] Example 4
[0051] The specific operation steps are the same as those in Example 3, except that 2 g of yttrium nitrate, 1.5 g of tantalum nitrate, 7 g of zirconium nitrate, 2.5 g of silver nitrate, and 0.7 g of strontium nitrate are dissolved in deionized water.
[0052] Example 5
[0053] The specific operation steps are the same as those in Example 3, except that 3 g of yttrium nitrate, 1 g of tantalum nitrate, 9 g of zirconium nitrate, 2 g of silver nitrate, and 0.9 g of strontium nitrate are dissolved in deionized water.
[0054] Example 6
[0055] The specific operation steps are the same as those in Example 3, except that yttrium is not added.
[0056] Example 7
[0057] The specific operation steps are the same as those in Example 3, except that 6 g of yttrium nitrate, 1.2 g of tantalum nitrate, 8 g of zirconium nitrate, 0.5 g of silver nitrate, and 1.7 g of strontium nitrate are dissolved in deionized water.
[0058] Comparative Example 1
[0059] The other operation steps are consistent with those in Example 3, except that the innermost pure titanium layer is removed during the coating process.
[0060] Example 8
[0061] The other operation steps are consistent with those in Example 3, except that the thickness of the pure titanium layer is 0.07 μm, and the thickness of the pure tantalum layer and the tantalum-yttrium alternating layer are also 0.07 μm.
[0062] Example 9
[0063] The other operation steps are consistent with those in Example 3, except that: 15 alternating layers are formed.
[0064] Example 10
[0065] The other operation steps are the same as those in Example 3, except that the content of tantalum pentoxide is 50 wt % and the content of yttrium trioxide is 50 wt %.
[0066] Experimental Example 1
[0067] The properties of the final product materials made by the above embodiment and the comparative example are compared, as shown in Table 1 below. The bone replacement implant material formed by the untreated TC4 titanium alloy and the polymer polyethylene is tested to have a tensile strength of 737 MPa and a yield strength of 850 MPa:
[0068] The antibacterial rate of Staphylococcus aureus is tested according to the method in the national standard "Food Microbiology Test for Staphylococcus aureus" (GB4789.10-2016). The antibacterial rate of Escherichia coli is tested according to the method in the national standard "National Food Safety Standard Food Microbiology Test for Coliform Count" (GB4789.3-2010).
[0069] The corrosion rate was tested under conditions of simulated body fluids, using PBS (phosphate buffered saline) for preparation, with the pH controlled at 7.4 to simulate the pH environment of the human body. The experimental temperature was set at 37°C, and the specimens were completely immersed in the prepared simulated body fluids. After soaking for one week, the specimens were taken out and the corrosion rate was analyzed and recorded.
[0070]
[0071] It can be seen from Table 1 above that the implant material of the present invention has excellent toughness and strength, and good antibacterial properties, indicating that the bonding force between the matrix and the membrane is also strong. It can be seen from the results of Example 6 that without the addition of yttrium, it is impossible to better cooperate with other metals to achieve the effects of bonding, corrosion resistance and antibacterial properties, so it can be seen that each component is indispensable in the formula combination.
[0072] It can be seen from the results of Example 7 that the amount of yttrium nitrate and silver nitrate added is larger than that of Example 3, and the amount of strontium nitrate added is too small. The addition of strontium metal promotes biocompatibility. If the amount added is insufficient, it will affect the stability of the material itself. At the same time, too much silver and yttrium added will cause the antibacterial and corrosion resistance of the material itself to be unbalanced, which will affect the overall performance of the material itself. Therefore, it can be seen from this embodiment that each component needs to be controlled within an appropriate proportion.
[0073] From the data of Examples 8-9 and Comparative Example 1, it can be seen that when the pure titanium layer is not added, or the thickness is inappropriate, or the number of alternating layers is too many, the performance of the material itself will be affected. This is because the pure titanium layer is mainly for corrosion resistance, and its anti-corrosion effect is obvious. Moreover, after being bonded to the substrate, it has a good effect on improving the performance of the sample, so this layer is indispensable. Similarly, considering its different position with the substrate, its thickness also needs to be set differently. If the setting is unreasonable, it will affect the tuberculosis. In addition, if the number of alternating layers is too many, it will affect the operability and will not have any further effect on the performance improvement. Therefore, the number of alternating layers should not be too thick.
[0074] It can be known from the data of Example 10 that the contents of tantalum pentoxide and yttrium trioxide need to be properly proportioned according to the scheme of the present invention. This is because in the whole process of compounding the components, yttrium trioxide mainly plays an auxiliary role, so its addition amount should not be too large, otherwise it will affect the overall performance of the sample.
[0075] Finally, it is understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the principles and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A method for processing polymer implant material samples, characterized in that: The steps include: The polymer matrix material is immersed in a nitrate solution containing metal ions at a temperature of 40-50° C. for more than 10 hours, and the surface is coated after the immersion, wherein the metal ions include any one or more of yttrium, tantalum, zirconium, silver, and strontium metal elements, and the polymer matrix material includes at least an alloy; The coating includes a pure titanium layer as an innermost layer, a pure tantalum layer as an intermediate layer, and a tantalum-yttrium alternating layer as an outermost layer.
2. The method for processing polymer implant material samples according to claim 1, characterized in that: The composition of the metal ions includes: by mass, 1-5 parts of yttrium, 0.5-2 parts of tantalum, 5-10 parts of zirconium, 1-3 parts of silver, and 0.5-1 parts of strontium.
3. The method for processing polymer implant material samples according to claim 2, characterized in that: In terms of mass, the components include 2-3 parts of yttrium, 1-1.5 parts of tantalum, 7-9 parts of zirconium, 2-2.5 parts of silver, and 0.7-0.9 parts of strontium.
4. The method for processing polymer implant material samples according to claim 2, characterized in that: In terms of mass, there are 2.5 parts of yttrium, 1.2 parts of tantalum, 8 parts of zirconium, 2.2 parts of silver, and 0.8 parts of strontium.
5. The method for processing a polymer implant material sample according to any one of claims 1 to 4, characterized in that: The concentration of the nitrate solution is 20-30 wt%.
6. The method for processing a polymer implant material sample according to any one of claims 1 to 4, characterized in that: The thickness ratio of the pure titanium layer, the pure tantalum layer, and the tantalum-yttrium alternating layer is 1:(2-3):(2-5).
7. The method for processing polymer implant material samples according to claim 6, characterized in that: The number of layers of the tantalum-yttrium alternating layers that alternate with each other is 3-8, wherein the tantalum layer in the tantalum-yttrium alternating layers is attached to the pure tantalum layer.
8. The method for processing polymer implant material samples according to claim 6, characterized in that: The thickness of the pure titanium layer is 0.05-0.08 μm, preferably 0.07 μm.
9. The method for processing polymer implant material samples according to claim 6, characterized in that: The content of tantalum pentoxide in the tantalum-yttrium alternating layer is 60-70wt%, and the rest is yttrium.
10. The method for processing a polymer implant material sample according to any one of claims 1 to 9, characterized in that: Each layer of the coating is sputtered using a corresponding target material.
Citation Information
Patent Citations
Antibacterial dental implant abutment
CN108095843A
Medical coating applied to implanted medical instrument and preparation method of medical coating
CN111632205A
Manufacturing method and application of metal powder
CN114247893A
Multilayer-structure tantalum-silver film implanted into surface of medical device and preparation method of multilayer-structure tantalum-silver film
CN116688229A
Medical bone plate with metal coating
CN215131141U